Autogenic Relaxation, Movement, and Affirmation (RIMA) Therapy: Efforts to Strengthen Self-Efficacy to Prevent Drug Withdrawal in Aggregate Patients with Pulmonary TB - Siti Kholifah; Putu Sintya Arlinda Arsa (Babali Nursing Research, 2022)
Introduction: Strengthening self-efficacy is an alternative to prevent drug withdrawal in patients with pulmonary TB. Autogenic relaxation, movement and affirmation (RIMA) therapy can help strengthen self-efficacy in patients with pulmonary TB so as to prevent drug withdrawal. The general objective of this study was to determine the role of RIMA therapy in strengthening the self-efficacy of pulmonary TB patients. Methods: The design of this research is a quasi-experimental using pre-test and post-test with control group design. The Respondents were patients with pulmonary TB in the work area of the Puskesmas Pakis, Malang Regency, a total of 60 people were determined using purposive sampling. RIMA therapy was carried out for 2 weeks, and data collection was carried out using a questionnaire. Data analysis used Wilcoxon Signed Rank test and Mann-Whitney test with α = 0.05%. Results: The results of this study indicate that there is an effect of RIMA therapy on self-efficacy in the experimental group, which is indicated by a p value = 0.000 (< 0.05). In addition, there is a significant difference in self-efficacy between the experimental group and the comparison group, which is indicated by the p value = 0.000 (< 0.05). Conclusion: RIMA therapy influences increasing self-efficacy of pulmonary TB patients. Therefore, it is recommended that patients with pulmonary TB carry out RIMA therapy independently at home to support their treatment.